Initial therapeutic target attainment of perampanel in pediatric patients with epilepsy - Yu, Lingyan; Chen, Meng; Liu, Jieqiong; Yu, Zhenwei; Feng, Jianhua; Dai, Haibin (Frontiers in Pharmacology, 2023)
Perampanel is a promising option for the treatment of pediatric epilepsy, but its plasma concentration varies among patients. This retrospective study aimed to investigate the initial target attainment of perampanel plasma concentration in pediatric patients with epilepsy in China. Inpatients admitted from January 2020 to December 2021 in a tertiary hospital were retrospectively included according to pre-set criteria. Demographic characteristics of patients and dosing strategies and therapeutic drug monitoring results were collected. A total of 137 pediatric patients (84 females and 53 males, aged from 0.6 to 16.4 years) were include for analysis. The perampanel concentrations varied greatly from 60 to 1560 mg/L among patients, but 89.8% had suitable perampanel concentrations (100-1000 ng/mL). The concomitant use of enzyme-inductive antiepileptic drugs (AEDs) was the only identified risk factor associated with target nonattainment (OR=5.92, 95% confidence interval 1.68-20.9). Initial perampanel target attainment in pediatric patients is satisfactory. Routine therapeutic drug monitoring to achieved the suggested concentration range for these patients may be unnecessary, except for those receiving combined enzyme inductive AEDs.